Normalization of Mendeley reader impact on the reader- and paper-side: A comparison of the mean discipline normalized reader score (MDNRS) with the mean normalized reader score (MNRS) and bare reader counts. Issue 3 (August 2016) - Bornmann, Lutz; Haunschild, Robin
Highlights: Mendeley reader counts – an important altmetric source – are field-dependent and are normalized in this study. The mean discipline normalized reader score (MDNRS) – an adaptation of the citing-side normalization – is introduced. Each reader is weighted with discipline-specific reader densities for the calculation of the MDNRS. The MDNRS is compared with the paper-side normalization of reader counts (MNRS) and bare reader counts. The MNRS is able to normalize reader counts in all disciplines. Abstract: For the normalization of citation counts, two different kinds of methods are possible and used in bibliometrics: the cited-side and citing-side normalizations both of which can also be applied in the normalization of "Mendeley reader counts". Haunschild and Bornmann (2016a) introduced the paper-side normalization of reader counts (mean normalized reader score, MNRS) which is an adaptation of the cited-side normalization. Since the calculation of the MNRS needs further data besides data from Mendeley (a field-classification scheme, such as the Web of Science subject categories), we introduce here the reader-side normalization of reader counts which is an adaptation of the citing-side normalization and does not need further data from other sources, because self-assigned Mendeley disciplines are used. In this study, all articles and reviews of the Web of Science core collection with publication year 2012 (and a DOI) are used to normalize their Mendeley reader counts. The newly proposed indicator (mean discipline normalized reader score, MDNRS) is obtained, compared with the MNRS and bare reader counts, and studied theoretically and empirically. We find that: (i) normalization of Mendeley reader counts is necessary, (ii) the MDNRS is able to normalize Mendeley reader counts in several disciplines, and (iii) the MNRS is able to normalize Mendeley reader counts in all disciplines. This generally favorable result for the MNRS in all disciplines leads to the recommendation to prefer the MNRS over the MDNRS—provided that the user has an external field-classification scheme at hand.